Factors associated with treatment outcomes of patients with drug-resistant tuberculosis in China: A retrospective study using competing risk model - Li, Zhiwei; Lai, Keng; Li, Tiegang; Lin, Zhuochen; Liang, Zichao; Du, Yuhua; Zhang, Jinxin (Frontiers in Public Health, 2022)
Objectives: Drug-resistant tuberculosis remains a serious public health problem worldwide, particularly in developing countries, including China. This study determined treatment outcomes among a cohort in Guangzhou, China, and identified factors associated with them. Methods: We initiated a retrospective study using drug-resistant TB data in Guangzhou from 2016 to 2020, managed by Guangzhou Chest Hospital. A competing risk model was used to identify the factors associated with treatment failure and death, as well as loss to follow-up. Results: A total of 809 patients were included in the study, in which 281 were under treatment. Of the remaining 528, 314 (59.5%) were treatment success, 14 (2.7%) were treatment failure, 32 (6.0%) were death and 168 (31.8%) were loss to follow-up. Being older and with the cavities involving the upper lungs were risk factors of treatment failure and death, while non-Guangzhou household registration and interprovincial mobility were risk factors associated with loss to follow-up. Conclusions: Treatment failure and death were significantly associated with Cavity and LTFU with household registration and mobility. Early identification of factors associated with different treatment outcomes is extremely important for policymakers, health experts, and researchers to implement appropriate strategies and measures to treat and manage the TB infected population in China.